Analisis Faktor- Faktor Yang Mempengaruhi Minat Mahasiswa Berkarir Sebagai Akuntan Publik (Studi Kasus Pada Mahasiswa Ekonomi Akuntansi Universitas Stikubank Semarang) - Sari, Putri Natalia Printania; Nugroho, Arief Himmawan Dwi (Jurnal Economic Resource, 2025)
Public accountants are one of the career choices for accounting graduates. However, students' decision to become public accountants is influenced by many factors. The purpose of this research is to analyze the influence of financial rewards, market considerations, work environment, and personality on the interest in becoming a public accountant. The research method uses a quantitative research type. The sample in this study is 100 accounting students from Stikubank University. The data collection technique uses a questionnaire. The data analysis technique uses multiple linear regression analysis. The research results show that partially, financial rewards, market considerations, work environment, and personality have a significant influence on the interest in becoming a public accountant. The extent of the influence of financial rewards, market considerations, work environment, and personality on the interest in becoming a public accountant is 71.7%.